2012
DOI: 10.1007/s11999-012-2632-9
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Osteochondral Avulsion Fracture of the Posteromedial Bundle of the PCL in Knee Hyperflexion

Abstract: Background Injury of the PCL of the knee in adults usually results in rupture rather than avulsion fracture and avulsions usually occur at the tibial insertion. Case Description We report an avulsion of the PCL with a femoral origin in a 22-year-old man who was injured by hyperflexion of the knee and was treated with arthroscopy. There were two parts in the partial osteochondral avulsion fracture of the PCL posteromedial (PM) bundle. One part was fixed with polydioxanone suture through drill holes and the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…In 2009, Lee et al 8 reported a case of a 22-year-old soldier in which imaging had revealed bony fragments and an osteochondral defect in the medial femoral condyle which on arthroscopic evaluation was found to be originated from medial femoral condyle with a connection to the PCL fiber. In 2012, Xu et al 9 reported an avulsion of the PCL from femoral origin in a 22-year-old man.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Lee et al 8 reported a case of a 22-year-old soldier in which imaging had revealed bony fragments and an osteochondral defect in the medial femoral condyle which on arthroscopic evaluation was found to be originated from medial femoral condyle with a connection to the PCL fiber. In 2012, Xu et al 9 reported an avulsion of the PCL from femoral origin in a 22-year-old man.…”
Section: Discussionmentioning
confidence: 99%
“…OCFs involve trauma to the articular surface (Schuett et al, 2015;Toritsuka, Horibe, Hiro-oka, Mitsuoka, & Nakamura, 2007). Avulsion fractures are a fairly common type of injury to the knee (Heckman & Alkire, 1984;Keshkar, Dey, & Kumar, 2014;Toritsuka et al, 2007;Xu, Chen, Shi, & Jiang, 2012) and occur as the tendons can tolerate more stress than muscle tissue (Coleman & Rodeo, 2003:216). Following Millgram's description of avulsion fractures, where the patella experiences lateral subluxation, Heckman and Alkire (1984:426-427) suggest that the bone will experience spontaneous reduction and shear off part of the bone.…”
Section: Ocfmentioning
confidence: 99%
“…The possible trauma mechanism of acute tibial avulsion fracture of the PCL is similar to isolated PCL injury, including a direct anterior tibial force to a flexed knee, knee hyperflexion with a downward force on the thigh, or knee hyperextension. 9 A midsubstance tear of the PCL is most often attributed to lower-energy injuries, whereas an avulsion-type injury pattern usually occurs during high-energy trauma. 10,11 During the clinical examination, a complete physical examination of the knee is performed to evaluate any potential concomitant lesions.…”
Section: Preoperative Workup and Planningmentioning
confidence: 99%